Feature-preserving multilevel halftoning algorithm - Wong, Lai-Yan; Chan, Yuk-Hee (Journal of electronic imaging, 2012)
Conventional threshold decomposition-based multilevel halftoning algorithms decompose an input image into layers, halftone each one of them with a binary halftoning algorithm, and combine their binary halftones to produce the final multilevel halftone. As layers are handled one by one subject to a stacking constraint, darker pixels in the final multilevel output are positioned first, which makes it difficult for the algorithms to preserve bright spatial features. This issue is addressed and a solution to eliminate this bias is proposed. Simulation result shows that the proposed method can provide an output of better quality as compared with conventional threshold decomposition-based algorithms both subjectively and objectively.